2012
DOI: 10.15288/jsad.2012.73.675
|View full text |Cite
|
Sign up to set email alerts
|

Do Substance Use Norms and Perceived Drug Availability Mediate Sexual Orientation Differences in Patterns of Substance Use? Results from the California Quality of Life Survey II

Abstract: ABSTRACT. Objective: Illicit drug and heavy alcohol use is more common among sexual minorities compared with heterosexuals. This difference has sometimes been attributed to more tolerant substance use norms within the gay community, although evidence is sparse. The current study investigated the role of perceived drug availability and tolerant injunctive norms in mediating the linkage between minority sexual orientation status and higher rates of prior-year substance use. Method: We used data from the second C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 64 publications
3
70
0
1
Order By: Relevance
“…However, neighborhood drug activity has not been linked, consistently, to increased drug use among African American young persons (Crum et al, 1996;Furr-Holden et al, 2014;Lambert, Brown, Phillips, & Ialongo, 2004;Ridenour et al, 2009). Thus, while drugs may be more readily available in neighborhoods with drug activity, the simple assumption that exposure to drug activity increases drug use may not be correct (Cochran et al, 2012;Crum et al, 1996;Wagner & Anthony, 2002;Wertz & Sayette, 2001). This relationship is likely complex and requires consideration of the synergistic effects of exposure, intra-person factors (e.g., neurobehavioral traits), and other social and cultural factors (Mennis & Mason, 2012;Ridenour et al, 2009Ridenour et al, , 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, neighborhood drug activity has not been linked, consistently, to increased drug use among African American young persons (Crum et al, 1996;Furr-Holden et al, 2014;Lambert, Brown, Phillips, & Ialongo, 2004;Ridenour et al, 2009). Thus, while drugs may be more readily available in neighborhoods with drug activity, the simple assumption that exposure to drug activity increases drug use may not be correct (Cochran et al, 2012;Crum et al, 1996;Wagner & Anthony, 2002;Wertz & Sayette, 2001). This relationship is likely complex and requires consideration of the synergistic effects of exposure, intra-person factors (e.g., neurobehavioral traits), and other social and cultural factors (Mennis & Mason, 2012;Ridenour et al, 2009Ridenour et al, , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…One unique characteristic of economically disadvantaged African American neighborhoods that is conceptualized as a risk factor for substance use is visible drug market activity (Crum, Lillie-Blanton, & Anthony, 1996;Saxe et al, 2001;Wallace & Muroff, 2002;Wertz & Sayette, 2001). In lower socioeconomic (SES) neighborhoods with visible drug activity there are more opportunities to use drugs and drug sub-cultures likely reduce inhibitions about drug use, thereby increasing the likelihood of use (Wagner & Anthony, 2002;Linton, Jennings, Latkin, Gomez, & Mehta, 2014;Wertz & Sayette, 2001;Cochran, Grella, & Mays, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research conducted with the general population of MSM has reported that incongruence often exists between orientation, self-identification, and behaviors. This incongruence may be one of the factors that contributes to the high rates of mental health issues (including substance use) that exists among MSM (Cochran et al 2012; Marshall et al, 2008; McCabe et al, 2010). A more complete comparison of substance abuse behaviors between heterosexual Hispanic men and Hispanic MSM is necessary that includes sexual identification, sexual attraction, and sexual behaviors.…”
Section: Limitationsmentioning
confidence: 99%
“…1 Drug-related law enforcement has been associated with negative health outcomes 23,4 and has been scrutinized for being disproportionately targeted in low-income minority communities. 1 Inequities in the targeting of drug-related law enforcement have partly been attributed to the extent to which drug market activity is visible.…”
Section: Introductionmentioning
confidence: 99%
“…10 Perceived opportunities to use illicit drugs have been associated with urges to use illicit drugs 22 and social norms supportive of use. 23 Through such pathways, visible drug activity may encourage illicit drug use. Additionally, the purveyance of social disorder, physical disorder, economic deprivation, and increased likelihood of incarceration in areas with high visible drug activity may further lead to poor drug-related sequelae.…”
Section: Introductionmentioning
confidence: 99%